Personal Precautionary Measures in the Context of Transnational Organized Corruption: Some Proposals and Reflections Based on Comparative Analysis - Beltrán Calfurrapa, Ramón (2025)
The aim of this article is to analyze, from a comparative perspective, personal preventive measures and their regulation in the context of corruption associated with transnational organized crime. To achieve this, two closely related factors will be addressed: on the one hand, the political-criminal projection of these precautionary measures in the crime of corruption associated with transnational organized crime and, on the other hand, how and in what way different countries regulate their concurrence and application in this type of crime. In this way, together with a critical assessment of their foundations and criteria of correctness, it will be concluded that only through the establishment of homogeneous and uniform guidelines will it be possible to ensure that these preventive measures are effectively applied against this type of crime.